Solidaritas Masyarakat Banjar Di Kuin Dalam Tradisi Baayun Maulid - Mahdalena, Kartika Sindi; Hakim, Arif Rahman (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
Baayun Maulid is an annual tradition held every month of Mulud or usually called Maulid by the Kuin Community. This research is located in North Kuin and uses qualitative research with a descriptive approach. The theory used is the theory put forward by Emile Durkheim. Data collection was carried out through participant observation, in-depth interviews, and documentation. Data analysis uses the Miles and Huberman model. The results of this research show that in the process of implementing Baayun Maulid, there is a process before the event of carrying out mutual cooperation activities. The Baayun Maulid event was attended by distinguished guests, the Mayor of Banjarmasin and his staff as well as various other groups including religious leaders, the Kuin community and people outside Kuin. After the Baayun Maulid event, the community carried out mutual cooperation activities again to clean the place that had been used during yesterday's Baayun Maulid event. It can be seen from the form of solidarity, a very strong collective awareness mechanism, where the Kuin community has the awareness to respect obedience because of very high religious values, and there are collective habits of behavior that have become habits that help when there are events in the Kuin community. such as in the process before the event, the community works together to set up tents, decorate swings and provide food by the community. Apart from the form of mechanical solidarity, it can also be seen in the form of organic solidarity, collective awareness is very low, which can be seen using services such as renting tents, renting swing setters and catering. This is interdependence and cooperation between individuals based on common interests.